Biomechanical Comparison of Low-Profile Contoured Locking Plate With Single Compression Screw to Fully Threaded Compression Screws for First MTP Fusion. (July 2019) - Fuld, Richard S.; Kumparatana, Pam; Kelley, Judas; Anderson, Nicholas; Baldini, Todd; Younger, Alastair S. E.; Hunt, Kenneth J.
Background: Open metatarsophalangeal (MTP) arthrodesis using locked plates produces good clinical outcomes. However, arthroscopic fusion with new-generation fully threaded compression screws is emerging as an alternative. The purpose of this study was to compare low-profile contoured locked plates with fully threaded compression screws for first MTP fusion, in a biomechanical cadaveric model. Methods: The first rays of 8 matched pairs of fresh frozen cadaveric feet underwent dissection and dual-energy x-ray absorptiometry (DEXA) scanning to measure bone mineral density (BMD). The "plate" group was prepared with cup-and-cone reamers, and fixation of the MTP joint with 1 compression screw and low-profile dorsal locked plate. The matched-pair "screws" group was prepared through a simulated arthroscopic technique, achieving fixation with 2 new-generation fully threaded compression screws. The plantar MTP gap was recorded with an extensometer during 250 000 90-N cyclic loads followed by a single load to failure. Results: The screw group demonstrated significantly greater stiffness, 31.6 N/mm (plates) and 51.7 N/mm (screws) ( P = .0045). There was no significant difference in plantar gapping or load to failure, 198.6 N (plates) and 290.1 N (screws) ( P = .2226). Stiffness and load to failure were highly correlated to BMD for the screw group, r =0.79 and r = 0.94, respectively, but less so for the plate group, r = 0.36 and r = 0.62, respectively. The maximum metatarsal head height measured on the lateral view was strongly correlated with load to failure for both the plate- and screw-only groups ( r > 0.9). Conclusion: These data demonstrate that hallux MTP arthrodesis utilizing fully threaded compression screws had similar plantar gapping and load to failure when compared with the low-profile locking plate, but with significantly more stiffness. These results support an increased role of fully threaded screws for MTP arthrodesis using either the arthroscopic or open technique. However, with decreased BMD plate fixation may remain the better fixation choice. Clinical Relevance: Our data suggest that with regard to construct stability, fully threaded headless compression screws may be just as effective as low-profile locking plates, but BMD and MTP joint fluoroscopic measurements should be considered in the decision-making process for fixation.